Optimum design of morphing flaps for improving horizontal axis wind turbine performance - Arezoo Najafian; Alireza Jahangirian (Energy Science & Engineering, 2023)
Abstract This study presents a conceptual design of optimum deformable blades as a function of wind speed. In this design, at any speed of wind flow, the blade sections have their optimal shape. Accordingly, the wind turbine performance will increase at different speeds. The WindPACT 1.5‐MW wind turbine is used as the base turbine, which has three different sections at the root, middle, and tip of the blade. The proposed deformation method, due to its simplicity, is suitable for the use of actuators. Different deflection angles are obtained at various wind speeds for each section through a controllable flap deformation method. The blade element momentum theory is used to calculate the performance of the morphing flaps. The results of this design are then validated by computational fluid dynamics (CFD) simulations using three‐dimensional Reynolds averaged Navier–Stokes equations together with the k–w turbulence model. The CFD results show that using optimum flap angles between 2° and 8° in the root, middle, and tip parts of the blade leads to a promising power increase of about 1.2%, 3.7%, and 13.5% at wind speeds of 4, 8, and 11.5 m/s.